Monoclonal Antibody Therapy for COVID-19: A Public Health Perspective From Arkansas. (10th January 2022) - Kothari, Atul; Woodland Borella, Elizabeth; Smith, Michelle R
Abstract: COVID-19 monoclonal antibodies revolutionized the treatment for eligible patients who have tested positive for SARS CoV-2 infection in an ambulatory setting. In this short report, we describe our experience assisting in the distribution of monoclonal antibodies in Arkansas during the summer surge of the delta variant.